Enhancing Environmental Sustainability in a Critical Region: Climate Change Impacts on Agriculture and Tourism - Kazem Javan; Mehrdad Mirabi; Sajad Ahmad Hamidi; Mariam Darestani; Ali Altaee; John Zhou (Civil Engineering Journal, 2023)
The Ardabil Plain is pivotal in the national agricultural sector and ranks among the leading agricultural and horticultural production provinces. The primary objective of this study is to enhance environmental sustainability in this critical and vulnerable region, particularly in the face of imminent droughts and climate change. The study examines the impacts of climate change on agriculture and tourism in the area. It puts forward suggestions for implementing sustainable practices to safeguard the well-being of the local population. The results indicate a 38% reduction in precipitation, especially in the autumn season, with a possible alteration in the timing and strength of rainfall. Also, a notable decline in production volume, particularly in a specific region of the Ardabil plain, has been observed. The Ardabil Plain currently produces 284,182 tons of wheat, with 204,980 tons from irrigated crops and 79,202 tons from rain-fed crops. However, the projected future scenario indicates a decrease in total wheat production to 209,196 tons, with 160,125 tons from irrigated crops and 49,071 tons from rain-fed crops. This decline in production is expected to lead to a total net income loss of approximately -$75,389,059, with -$45,095,663 attributed to irrigated crops and -$30,293,396 to rain-fed crops. The study findings suggest that the availability of water sources in certain regions may prompt a shift in farming land from the north to the south of the plain to promote environmental sustainability. This demographic change could have significant financial and social implications for the region's growth and prosperity. Moreover, increasing temperatures in the western and northern regions pose flood risks and uncomfortable travel conditions, particularly concerning given the reliance on tourism and potential unemployment consequences. It becomes imperative to adopt sustainable practices and manage resources effectively to ensure the region's resilience and prosperity in the face of environmental challenges. Doi: 10.28991/CEJ-2023-09-11-01 Full Text: PDF